Commonly available dietary supplements, herbs and medicines – do they pose a risk for liver health? Literature review in the context of the Polish population - Ewa Janczewska; Barbara Janota (Clinical & Experimental Hepatology)
Liver injury resulting from the use of dietary supplements, herbs, and commonly available medications is a problem that is becoming increasingly significant due to the widespread availability and growing popularity of these products. Factors contributing to this damage may include supplements used for weight reduction, questionable quality herbs, and commonly available pain-relief and anti-inflammatory medications. Currently, the most appropriate solution to this problem appears to be prevention by patient education and medical community awareness, as well as increased oversight of the market for these types of products.